bài 1: giải các phương trình sau
a)10+3(x-2)=2(x+3)-5 b)5/x-3+4/x+3=x-5/x^2-9 c)2x(x+2)-3(x+2)=0
bài 2 giai cac bat phuong trinh sau va bieu dien no tren truc so
a)2(3x-2)<3(4x-3)+11 b)x+3/4-13-x/12 ≥2x-1/3
bài 1: giải các phương trình sau
a)10+3(x-2)=2(x+3)-5 b)5/x-3+4/x+3=x-5/x^2-9 c)2x(x+2)-3(x+2)=0
bài 2 giai cac bat phuong trinh sau va bieu dien no tren truc so
a)2(3x-2)<3(4x-3)+11 b)x+3/4-13-x/12 ≥2x-1/3
Bài `1`:
`a)` `10`+`3(x-2)`=`2(x+3)-5` ⇔ `10+3x-6`=`2x+6-5`
⇔ `3x`-`2x`=`6`-`5`-`10`+`6` ⇔ `x`=`-3`
`b)“2x(x+2)-3(x+2)=0` ⇔ `(x+2)(2x-3)`=`0`
⇔ \(\left[ \begin{array}{l}x+2=0\\2x-3=0\end{array} \right.\)
⇔ \(\left[ \begin{array}{l}2x-3=0\\x=3/2\end{array} \right.\)
Bài `2`:
`a)“2(3x-2)<3(4x-3)+11`⇔`6x-4<12x-9`
⇔ `6x-12x<4-9` ⇔ `-6x<-5`
⇔ `6x -5` ⇔ `x`.`5/6`
Bài 1:
a) 10+3(x-2)=2(x+3)-5<=>10+3x-6=2x+6-5
<=>3x-2x=6-5-10+6<=>x=-3
c)2x(x+2)-3(x+2)=0<=>(x+2)(2x-3)=0
<=>[x+2=0 <=>[x=-2
[2x-3=0 [x=3/2
Bài 2:
a)2(3x-2)<3(4x-3)+11<=>6x-4<12x-9
<=>6x-12x<4-9<=>-6x<-5
<=>6x>5<=>x>5/6